2006
DOI: 10.1094/cm-2006-0525-01-rs
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Fertilizer Management and Recommendations for Wheat Production in Central Mexico

Abstract: The current N fertilizer recommendation for wheat (Triticum aestivum L.) production in the central highlands of Mexico is to apply 71 lb N per acre. However, this N rate appears to exceed current crop needs. Therefore, research activities in farmers’ fields to estimate the optimum N rate and timing were initiated in 1999 and continued until 2002. A field trial was conducted at eleven location‐years representing the major wheat production areas of central Mexico. Four N rates were applied (0, 36, 63, and 89 lb … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Therefore, a fine‐tuning of N to overcome the effects of the stabilization period is not much an issue for an average of 2360 kg ha −1 wheat crop. Actually, other reports have indicated that N fertilizer for rainfed environments with a grain yield potential of 3000 kg ha −1 or less, N fertilizer may not be needed as grain yield increase is minor (Limon‐Ortega and Villasenor‐Mir, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a fine‐tuning of N to overcome the effects of the stabilization period is not much an issue for an average of 2360 kg ha −1 wheat crop. Actually, other reports have indicated that N fertilizer for rainfed environments with a grain yield potential of 3000 kg ha −1 or less, N fertilizer may not be needed as grain yield increase is minor (Limon‐Ortega and Villasenor‐Mir, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Critical periods of N demand vary in crops and adjusting fertilization timing according to crop N requirements may reduce the risk of N loss and excessive N fertilizer application (Fageria and Baligar, 2005). For instance, the critical timing of N demand in spring wheat is between double ridge to terminal spikelet phases (between 20 and 45 days after seeding) (Limon-Ortega and Villaseñor-Mir, 2006), while in maize it ranges from 35 to 45 days after seeding (Richie et al, 1986). In malting barley, adjusting the amount of split-N application is necessary to ensure good malting quality (Baethgen et al, 1995).…”
Section: Aspects Of Management Systemsmentioning
confidence: 99%
“…According to Schillinger (2005), the number of heads is generally the most important yield component and is primarily affected by management practices such as seeding rates and N inputs (Zhang et al, 2007). One way to optimize tillering and yield component formation is through the timing of N application (Weisz et al, 2001;Limon-Ortega & Villaseñor-Mir, 2006). A regression analysis with grain yield suggests that attaining 350 heads/m 2 is key to achieving about 3500 kg/ha of wheat in the Mexican Plateau (Limon_ortega, 2011).…”
Section: Varietymentioning
confidence: 99%